TINJAUAN YURIDIS TERHADAP PEMBATASAN KEGIATAN UNJUK RASA OLEH MAJELIS DESA ADAT DALAM PERSPEKTIF HAK ASASI MANUSIA (KEPUTUSAN MAJELIS DESA ADAT PROVINSI BALI NOMOR: 08/SK/MDA-PBali/X/2020) - A.A. Mas Adi Trinaya Dewi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The purpose of writing this thesis is for these matters: (1) to find out and analyze the legal force of Kep. MDA 08/SK/MDA-PBali/X/2020 against traditional villages in Bali in relation to restrictions on demonstrations at the traditional village of Wewidangan; (2) to find out and analyze the existence of Kep. MDA. 08/SK/MDA-PBali/X/2020 which is viewed from the perspective of human rights. This thesis is classified as a normative research which uses 2 types of approaches, namely the statutory approach and the conceptual approach. The legal materials in this thesis were collected using document study techniques and then analyzed qualitatively. Based on the research results, it is known that Kep. MDA 08/SK/MDA-PBali/X/2020 has binding legal force against traditional villages in Bali. This opinion is based on 3 considerations, namely: (1) the arrangement of Kep. MDA 08/SK/MDA-PBali/X/2020 is in accordance with the theory of Catur Praja and in line with the concept of the rule of law; (2) according to the considerations from Kep. MDA 08/SK/MDA-PBali/X/2020, it is known that the a quo decree was born after the traditional village in Bali stipulates and enforces Pararem for the Prevention and Control of Gering Agung Covid-19; and (3) Kep. MDA 08/SK/MDA-PBali/X/2020 is an implementation of the Bali Mawacara principle as referred to in Regional Regulation Number 4 of 2019. Furthermore, Kep. MDA 08/SK/MDA-PBali/X/2020 could not be qualified as a violation of human rights. Based on the principle of siracausa, the International Covenant On Civil And Political Rights 1966, and the provisions of Article 28 J of the 1945 Constitution of the Republic of Indonesia, the a quo decision can actually be used as a means to respect, protect, and fulfill human rights for every Balinese citizen, especially karma desa, krama tamiu, and guests who are in the traditional village of wewidangan.